PENGARUH BEBAN KERJA FISIK DAN BEBAN KERJA MENTAL TERHADAP STRES KERJA MELALUI KELELAHAN KERJA SEBAGAI VARIABEL MEDIASI PADA KARYAWAN BAGIAN PRODUKSI CV. SURYA PELANGI KOTA PEKANBARU - Salsabila Nisrina; Daulay Nauli Iwan; Siregar Andreas Prima (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of physical workload and mental workload on work fatigue and work stress on employees of the production division of CV. Surya Pelangi Pekanbaru City. The population in this study includes all employees of the production division of CV. Surya Pelangi Pekanbaru City, which amounted to 50 people. Primary data collected by questionnaire as an instrument to prove the results of the study. To test this research hypothesis, path analysis (path analysis) was used with the help of SPSS version 26. The sampling technique used was the total sample method or made the entire population as a sample of 50 employees of the production division of CV Surya Pelangi Pekanbaru City.The results of this study indicate that: 1) Physical Workload has a positive and significant effect on Work Fatigue, 2) Mental Workload has a positive and significant effect on Work Fatigue, 3) Physical Workload has a positive and significant effect on Work Stress, 4) Mental Workload positive and significant effect on Work Stress, 5) Work Fatigue has a positive and significant effect on Work Stress, 6) Physical Workload has a positive and significant effect on work stress through Work Fatigue, 7) Mental Workload has a positive and significant effect on work stress through Fatigue Work.Keywords: Physical Workload, Mental Workload, Work Fatigue and Work Stress